EVALUATION OF A METHOD FOR MASS REARING Bracon kirkpatricki Wilkinson (Hymenoptera: Braconidae) - ASTUDILLO-M., ANA MILENA; VARGAS-G., HÉCTOR A.; JIMÉNEZ-V., JADES (Revista Colombiana de Entomología, 1993)
The mass rearing of Bracon kirkpatrickiWil kinson on larvae of Galleria mellonella (L.) was carried out in the Entomology Laboratory of the Universidad del Valle, at Cali, 970 masl with 27°C and 65% of relative humidity. The object of the work was to evaluate an efficient method that would guarantee the mass rearing of the parasitoid B. kirkpatrickion G. mellonella larvae, with a commercial projection. Metal containers became a very functional mechanism for the rearing of G. mellonella . In regard to the occupation of space, 0,100 m3 was achieved against 0,232 m3 with its equivalent in glass flasks,.although as far as the number of larvae produced is concerned, there were no marked differences between the systems. The most functional parasitation chamber was the large one (62 x 32 x 9 cm) with the potential to generate between 3200 and 4560 parasitoids daily, with a sex relation of 19:1d, and 68% parasitism, obtaining 5.0 parasitoids/larvae.